Triadic thinking and its relationship with sociodemographic variables of Business Administration students - Lemus - Quintero, Jennifer Andrea (Universidad Francisco de Paula Santander, 2021)
The objective of this document is to carry out analysis of triadic thinking and its relationship with sociodemographic variables of the Business Administration students of the Francisco de Paula Santander Ocaña University - UFPSO. The research started from the application of Waldemar De Gregori's methodological test and investigation of sociodemographic characteristics of the studied population. The results achieved allowed us to conclude that the UFPSO Business Administration students present a proportionality in the three types of minds despite the different social and demographic conditions in which they are found. However, it could also be seen that, slightly, there are quite emotional and good students generating ideas but not very risky in executing the action.